Structural Characteristics of Regenerated Roof and Distribution Law of Overburden Porosity in Downward Mining of a Bifurcated Coal Seam - Ru Hu; Jiwen Wu; Xiaorong Zhai; Wenbao Shi; Kai Huang (Geofluids)
During downward mining of a bifurcated coal seam, the roof of the lower coal seam is relatively broken and difficult to control due to the mining influence of the upper coal seam. Roof accidents occur frequently during mining of the lower coal seam, reducing mining efficiency. How to ensure safe and efficient mining of the lower coal seam is a significant issue. In this paper, overlying strata migration and fracture characteristics of the lower coal seam, the structure and stability of the regenerated roof, and porosity and permeability characteristics of the overlying strata under the mining influence of the upper coal seam are studied by using similar simulation tests. Results show that the overburden structure of the lower coal seam is altered due to the mining influence of the upper coal seam, and the regenerated roof of the lower coal seam is divided into three structural types from top to bottom, namely: intact rock mass+block fracture rock mass+loose rock mass (type I structure); intact rock mass+block fracture rock mass+loose rock mass+cataclastic rock mass (type II structure); and intact rock mass+block fracture rock mass+loose rock mass+cataclastic rock mass+slab-rent rock mass (type III structure). The stability of each type of rock mass structure is evaluated, and the stability of three types of rock mass structures is III > II > I. The overburden porosity and slurry permeability coefficient are relatively large at the cutting hole and stopping line. The porosity of the caving zone within 70 m of the cut hole and stopping line is greater than 5%, and the permeability coefficient is greater than 0.1 m/s. Based on differences in the surrounding rock porosity and permeability characteristics, the grouting difficulty of overburden is divided into three types of areas: extremely easy grouting areas, easy grouting areas, and difficult grouting areas. The results of this paper can provide reference for the stability evaluation of the regenerated roof and the selection of grouting treatment parameters for the broken roof under similar conditions.